Utilization of Plastic Waste as Soil Stabilization Material and Their Effect on Unconfined Compressive Strength Values - Woelandari Fathonah; Rama Indera Kusuma; Enden Mina; Nadia Fadillah (Applied Research on Civil Engineering and Environment (ARCEE), 2023)
The objective of this research was to improve the bearing capacity of the soil located on Kampung Juhut Street, Pandeglang Regency, which initially had a bearing capacity of 3.01%, through stabilization methods. The plastic powder was selected as an additive due to its non-cohesive characteristics, which counterbalance the cohesive nature of clay soil. The study aimed to identify the soil type and classification, evaluate the impact of soil physical properties, and examine the changes in unconfined compressive strength after incorporating plastic powder in proportions of 2%, 4%, 6%, 8%, and 10%, with curing durations ranging from 0 to 28 days. The results indicated that the soil belonged to the category of organic clay soils with moderate to high plasticity according to the USCS soil classification system. The plasticity index decreased from 22.9% to 12.2% at the 8% variation and 11.9% at the 10% variation. The initial unconfined compressive strength of the soil was 1.1 kg/cm2. The greatest improvement was observed at the 8% variation, resulting in an unconfined compressive strength value of 3.4 kg/cm2, indicating a highly rigid consistency.